Physical and Mechanical Therapies for Lower Limb Problems in Juvenile Idiopathic Arthritis: A Systematic Review (Protocol) - Fellas, Antoni; Coda, Andrea; Hawke, Fiona (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2015)
Background: Juvenile Idiopathic Arthritis is the most common chronic, autoimmune, inflammatory joint disease affecting children under 16 years of age. Children with juvenile idiopathic arthritis may present with severe lower limb joint disability and dysfunction. The evidence base for treating lower limb problems in juvenile idiopathic arthritis is growing, however is currently uncoordinated and difficult for clinicians to access. This paper reports a protocol to systematically review the evidence for physical and mechanical interventions for lower limb problems in juvenile idiopathic arthritis. Methods/Design: The following electronic databases will be searched for eligible studies: MEDLINE, EMBASE, Cochrane Central Registar of Controlled Trials, PUBMED and CINAHL. Randomised control trials and quasi randomised control trials of physical and mechanical interventions for lower limb problems in children with juvenile idiopathic arthritis will be included. Two authors will independently screen studies for eligibility for inclusion and assess the risk of bias. One author will extract and analyse statistical data, which will be checked by a second author. Discussion: This systematic review aims to establish a best-practice pathway of non-invasive and non-drug interventions for lower limb complications of juvenile idiopathic arthritis and to highlight the areas of greatest need for future research.
Keywords: juvenile idiopathic arthritis